Practice-Oriented Research in Tertiary Mathematics Education – An Introduction - Biehler, Rolf; Liebendörfer, Michael; Gueudet, Ghislaine; Rasmussen, Chris; Winsløw, Carl (Practice-Oriented Research in Tertiary Mathematics Education)

Framing Goals of Mathematics Support Measures - Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Schürmann, Mirko; Biehler, Rolf; Schaper, Niclas (Practice-Oriented Research in Tertiary Mathematics Education)

Practice-Oriented Research in Tertiary Mathematics Education

Lernvideos und ihre Erstellung - Das Projekt studiVEMINTvideos - Biehler, Rolf; Liebendörfer, Michael; Schmitz, A. (Mitteilungen der Gesellschaft für Didaktik der Mathematik)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Enriching videos with interactive questions to enhance students’ cognitive activity: concept and implementation - Liebendörfer, Michael; Profeta, Angelo; Krämer, Sandra; Schlüter, Sarah; Becher, Silvia; Biehler, Rolf; Mai, Tobias; Schmitz, Angela

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einführung in das WiGeMath-Projekt: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

Opportunities and Possibilities of a Network of Mathematical Learning and Support Centres in Germany - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (Sigma newsletter)

Mathematics learning support centres in Germany—an overview - Schürmann, Mirko; Gildehaus, Lara; Liebendörfer, Michael; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard; Kuklinski, Christiane; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Mathematics learning support centres (MLSC) are widely established and evaluated in English-speaking countries (such as the UK, Ireland and Australia). In most of these countries, several national surveys on MLSCs exist. They give an overview of the number of MLSCs as well as their characteristics in these countries. In Germany, there is a lack of studies on MLSCs and the landscape of MLSCs has not been described yet. This article presents basic information concerning counts of MLSCs and their characteristics at universities. Based on a three-step approach of analysing university homepages and additional personal contact via email or phone calls, we gathered typical MLSC features (e.g. staff quantities and qualification, opening and support hours, supported study programmes). We analysed 190 universities from a web-based register on study programmes. In total, we found 61 MLSCs located at 51 German universities. Another 16 support centres were specialized on mathematics didactics, which means they focussed on didactical and methodological support for preservice teacher students and often provided different teaching materials. Thirty-eight centres were located at universities (62.3%) and 23 MLSCs at universities of applied sciences and comparable universities (37.7%). The MLSCs were different in their sizes of staff and opening hours, and both the numbers of staff and the service hours differed greatly. The student groups MLSCs at German universities focus on differ concerning characteristics like study programme or semester. We will provide the main categories describing these groups. We seek to answer research questions concerning the characteristics of MLSCs in Germany and discuss the results compared to international findings. This information is useful for further international collaborative research, for example a standardized international survey. From a national perspective, these findings support networking and collaborations between the MLSCs as well. As some German MLSCs are facing financial cuts, these results might help in gaining additional funding.
Keywords: Education; General Mathematics

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (Proceedings of the Third Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2020, 12-19 September 2020))

studiVEMINTvideos – Mathematische Lernvideos zur Studienvorbereitung und Unterstützung im ersten Studienjahr - Biehler, Rolf; Liebendörfer, Michael; Schmitz, Angela; Fleischmann, Yael; Krämer, Sandra; Ostsieker, Laura; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2020)

LimSt – Ein Fragebogen zur Erhebung von Lernstrategien im mathematikhaltigen Studium - Liebendörfer, Michael; Göller, Robin; Biehler, Rolf; Hochmuth, Reinhard; Kortemeyer, Jörg; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (Journal für Mathematik-Didaktik)

Chancen und Möglichkeiten eines Netzwerks von Mathematischen Lernzentren in Deutschland - Bericht zum digitalen Lernzentrumsworkshop am 22.10.2020 - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (dghd-Newsletter)

Ein Kurzbericht aus dem Forschungsprojekt WiGeMath-Lernzentren als Unterstützungsmaßnahme für mathematikbezogenes Lernen in der Studieneingangsphase - Schürmann, Mirko; Schaper, Niclas; Liebendörfer, Michael; Biehler, Rolf; Lankeit, Elisa; Hochmuth, Reinhard; Ruge, Johanna; Kuklinski, Christiane (dghd-Newsletter)

Features of innovative lectures that distinguish them from traditional lectures and their evaluation by attending students - Kuklinski, Christiane; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Lankeit, Elisa; Leis, Elena; Schürmann, Mirko (Proceedings of CERME 11)

Psychologische Grundbedürfnisse im frühen Mathematikstudium - Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2018)

Auswirkungen von innovativen Vorlesungen für Lehramtsstudierende in der Studieneingangsphase - Liebendörfer, Michael; Kuklinski, Christiane; Hochmuth, Reinhard (Beiträge zum Mathematikunterricht 2018)

Motivationsentwicklung im Mathematikstudium - Liebendörfer, Michael

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

Verbundprojekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Kuklinski, Christiane; Lankeit, Elisa; Leis, Elena; Liebendörfer, Michael; Schürmann, Mirko (3. Auswertungsworkshop der Begleitforschung. Dokumentation der Projektbeiträge.)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathmatikbezogenes Lernen in der Studieneingangsphase : Schlussbericht: Teilprojekt A der Leibniz Universität Hannover, Teilprojekte B und C der Universität Paderborn: Berichtszeitraum: 01.03.2015-31.08.2018 - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Kuklinski, Christiane; Lankeit, Elisa; Leis, Elena; Liebendörfer, Michael; Schürmann, Mirko

CAS in der Hochschullehre - Ein Blick in die Praxis - Frühbis-Krüger, Anne; Kemper, Gregor; Koepf, Wolfram; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2018)

Minisymposium CAS in der Hochschullehre - ein Blick in die Praxis - Frühbis-Krüger, Anne; Liebendörfer, Michael (Computeralgebra-Rundbrief)

Perceived Competence and Incompetence in the First Year of Mathematics Studies: Forms and Situations - Liebendörfer, Michael; Hochmuth, Reinhard (Didactics of Mathematics in Higher Education as a Scientific Discipline - Conference Proceedings)

Interest development during the first year at university: do mathematical beliefs predict interest in mathematics? - Liebendörfer, Michael; Schukajlow, Stanislaw (ZDM)

A framework for goal dimensions of mathematics learning support in universities - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Kuklinski, Christiane; Khellaf, Sarah; Colberg, Christoph; Schürmann, Mirko; Rothe, Lukas (Proceedings of the Tenth Congress of the European Society for Research in Mathematics Education (CERME10, February 1 – 5, 2017))
Keywords: Ziele der Lehre

Mathe – nein danke? Interesse, Beliefs und Lernstrategien im Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael; Schukajlow, Stanislaw (Lehren und Lernen von Mathematik in der Studieneingangsphase)

Research in University Mathematics Education: The khdm - Biehler, Rolf; Hochmuth, Reinhard; Rück, Hans-Georg; Göller, Robin; Hoppenbrock, Axel; Liebendörfer, Michael; Püschl, Juliane (EMS Newsletter)

Abschreiben - ein Problem in mathematischen Lehrveranstaltungen? - Liebendörfer, Michael; Göller, Robin (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014 Beiträge zum gleichnamigen Symposium am 7. & 8. November 2014 an der Westfälischen Wilhelms-Universität Münster)

Eine alternative Einstiegsvorlesung in die Fachmathematik – Konzept und Auswirkungen - Göller, Robin; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2016)
Keywords: _tablet; Abschreiben

Abschreiben von Übungsaufgaben in traditionellen und innovativen Mathematikvorlesungen - Liebendörfer, Michael; Göller, Robin (Mitteilungen der Deutschen Mathematiker-Vereinigung)
Keywords: _tablet; Abschreiben

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)

Perceived Autonomy in the First Semester of Mathematics Studies - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the Ninth Congress of the European Society for Research in Mathematics Education)

Initiative Bottom-Up-Nachtreffen zum Doktorandenkolloquium der GDM - Braun, Eileen Angélique; Liebendörfer, Michael; Schorcht, Sebastian (Mitteilungen der Gesellschaft für Didaktik der Mathematik)

Mathematik als Werkzeug: Sicht- und Arbeitsweisen von Studierenden am Anfang ihres Mathematikstudiums - Liebendörfer, Michael; Ostsieker, Laura (Mit Werkzeugen Mathematik und Stochastik lernen – Using Tools for Learning Mathematics and Statistics)

The Mathematical Beliefs and Interest Development of Pre-Service Primary Teachers - Liebendörfer, Michael; Hochmuth, Reinhard; Kolter, Jana; Schukajlow, Stanislaw (Proceedings of the 38th Conference of the International Group for the Psychology of Mathematics Education an the 36th Conference of the North American Chapter of the Psychology of Mathematics Education)

Self-determination and interest development of first-year mathematics students - Liebendörfer, Michael (Oberwolfach Reports)

Vorstellung eines Fragebogens zur Erfassung von Lernstrategien in mathematikhaltigen Studiengängen - Liebendörfer, Michael; Hochmuth, Reinhard; Schreiber, Stephan; Göller, Robin; Kolter, Jana; Biehler, Rolf; Kortemeyer, Jörg; Ostsieker, Laura (Beiträge zum Mathematikunterricht 2014)

Instrumentenentwicklung zur Messung von Lernstrategien in mathematikhaltigen Studiengängen - Göller, Robin; Kortemeyer, Jörg; Liebendörfer, Michael; Biehler, Rolf; Hochmuth, Reinhard; Krämer, Jana; Ostsieker, Laura; Schreiber, Stephan (Beiträge zum Mathematikunterricht 2013: Vorträge auf der 47. Tagung für Didaktik der Mathematik)

Mathe – nein danke? Interesse im und am Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael (Mathematik im Übergang Schule / Hochschule und im ersten Studienjahr)

Interest and Self-Determination in the Transition to Studying Mathematics - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 37th Conference of the International Group for the Psychology of Mathematics Education)

Interest in Mathematics and the First Steps at the University - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 8th Conference of European Research in Mathematics Education)

Mathematikinteresse im 1. Studiensemester - Liebendörfer, Michael; Hochmuth, Reinhard (Beiträge zum Mathematikunterricht 2012 : Vorträge auf der 46. Tagung für Didaktik der Mathematik)

Training of student teaching assistants and e-learning via math-bridge – Two projects at the German Centre for Higher Mathematics Education - Biehler, Rolf; Hoppenbrock, Axel; Klemm, Juliane; Liebendörfer, Michael; Wassong, Thomas (CETL-MSOR Conference 2011)